Making the Case for Human-Aware Navigation in Warehouses - Fernandez Carmona, Manuel; Parekh, Tejas; Hanheide, Marc (Towards Autonomous Robotic Systems, 2019)
This work addresses the performance of several local planners for navigation of autonomous pallet trucks in the presence of humans in a simulated warehouse as well as a complementary approach developed within the ILIAD project. Our focus is to stress the open problem of a safe manoeuvrability of pallet trucks in the presence of moving humans. We propose a variation of ROS navigation stack that includes in the planning process a model of the human robot interaction.